Improved unmanned aerial vehicle control for efficient obstacle detection and data protection - Moldamurat, Khuralay; Atanov, Sabyrzhan; Akhmetov, Kairat; Bakyt, Makhabbat; Belgibekov, Niyaz; Zhumabayeva, Assel; Shabayev, Yuriy (Institute of Advanced Engineering and Science, 2024)
The article centers on the research objectives and tasks associated with developing a swarm control system for unmanned aerial vehicles (UAVs) utilizing artificial intelligence (AI). A comprehensive literature review was undertaken to assess the effectiveness of the